Fear the serpent: A psychometric study of snake phobia. (30th August 2016) - Polák, Jakub; Sedláčková, Kristýna; Nácar, David; Landová, Eva; Frynta, Daniel
Abstract: Millions of people worldwide suffer from specific phobias. Almost any stimulus may trigger a phobic reaction, but snakes are among the most feared objects. Half of the population feel anxious about snakes and 2–3% meet the diagnostic criteria for snake phobia. Despite such a high ratio, only one instrument is commonly used, the Snake Questionnaire (SNAQ). The aim of this study was to develop a standardized Czech translation, describe its psychometric properties and analyze the distribution of snake fears. In a counter-balanced design 755 respondents were asked to complete the English and Czech SNAQ (first or last) with a 2–3 month delay; 300 of them completed both instruments. We found excellent test-retest reliability (0.94), although the total scores differed significantly when the English version was administered first. The mean score was 5.80 and Generalized Linear Models revealed significant effects of sex and field of study (women and people with no biology education scored higher than men and biologists). A cut-off point for snake phobia as derived from a previous study identified 2.6% of the subjects as phobic. Finally, the score distribution was similar to other countries supporting the view that fear of snakes is universal. Highlights: Czech translation of the Snake Questionnaire shows good psychometric properties. The distribution of snake fear in the Czech sample is comparable to other countries. Women and people without biology education report higher fear of snakes than men and biologists. 2.6% of subjects reached a score characteristic for snake phobics.